2009
DOI: 10.1017/s1744133109990260
|View full text |Cite
|
Sign up to set email alerts
|

New Zealand’s Primary Health Care Strategy: early effects of the new financing and payment system for general practice and future challenges

Abstract: : Since 2001, implementation of a New Zealand's Primary Health CareStrategy (the Strategy) has led to an increase in the proportion of primary health care services which are publicly funded, the development of 82 primary health organisations (PHOs) to oversee primary health care services and universal public capitation funding of PHOs. This approach has replaced the previous system of fee-for service targeted public subsidies paid to individual general practitioners (GPs). Patient copayments, although at a red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 11 publications
0
27
1
1
Order By: Relevance
“…Access to primary health care improved as a result, with a general reduction in patient's fees for all patients from 2001 to 2007, a population-wide increase in the number of consultations per patient from 2001 to 2007, and levels of unmet need halving from 12% in 2002 to 6% in 2007 (Cumming et al, 2008;Cumming & Mays, 2009;New Zealand Ministry of Health, 2004. There is also evidence that equity of access has improved since 2001: fees dropped more for those attending practices, with high numbers of New Zealand Māori (the indigenous people), Pacific patients, and patients from the most deprived areas (Cumming & Mays, 2009).…”
mentioning
confidence: 99%
“…Access to primary health care improved as a result, with a general reduction in patient's fees for all patients from 2001 to 2007, a population-wide increase in the number of consultations per patient from 2001 to 2007, and levels of unmet need halving from 12% in 2002 to 6% in 2007 (Cumming et al, 2008;Cumming & Mays, 2009;New Zealand Ministry of Health, 2004. There is also evidence that equity of access has improved since 2001: fees dropped more for those attending practices, with high numbers of New Zealand Māori (the indigenous people), Pacific patients, and patients from the most deprived areas (Cumming & Mays, 2009).…”
mentioning
confidence: 99%
“…It is important to consider the international context and the extent to which the patterns of The most similar case to the Republic of Ireland is that of New Zealand (although the current primary care reforms in New Zealand are moving away from individual targeting of benefits towards universal targeting via Primary Health Organisations; see (Cumming et al, 2011) for a review). Prior to the current reforms in New Zealand, the community services card (CSC) operated in a similar manner to the Irish medical card, except that it covered a larger proportion of the population (approximately 50 per cent) and cardholders received a subsidy from the government for each GP visit (equivalent to approximately one third of the full cost), rather than free GP visits in the Irish case.…”
mentioning
confidence: 99%
“…Regression analysis has found that the CSC cardholders were significantly more likely to visit their GP, controlling for need and other socio-economic characteristics (Scott et al, 2003). Similar to the Irish concerns over take-up of the GP Visit card, the New Zealand CSC was also subject to low take-up, and this in part has motivated the movement towards universal targeting of subsidies for GP visits via higher capitation payments to Primary Health Organisations (Cumming et al, 2011). In many countries however, while GP visits may be free, prescription pharmaceuticals are subject to co-payments (similar to the situation for GP Visit card holders).…”
mentioning
confidence: 99%
“…In fact, staff in DHBs generally asked for more detail from the Ministry of Health on how to implement national policy on population health improvement rather than less, while complaining about the unwarranted degree of Ministry interference in other areas of DHB responsibility (Mays et al, 2007), particularly hospitals. One possible explanation for this relates to the level of challenge involved in developing and implementing policies in this area (eg the need for both 'horizontal' and 'vertical' integration of policy action at national, regional and local levels to respond to the wide-ranging determinants of population health and inequalities (Exworthy and Powell, 2004).…”
Section: Neither Clashes Nor Fits But Gapsmentioning
confidence: 99%